154k views
9 votes
2g + h =2
g -h= -5

find g and h step by step explanation​

User Marilena
by
5.1k points

1 Answer

6 votes

Answer:

Explanation:

2g + h = 2 --------------(I)

g - h = -5------------(II)

g = -5 + h

Plugin g = -5 + h in equation (I)

2(-5 + h) + h = 2 {Distributive property:a(b+c) = a*b +a*c}

(-5)*2 + h *2 + h= 2

-10 + 2h + h = 2

3h = 2 + 10

3h = 12

h = 12/3

h = 4

Substitute h= 6 in equation (I)

2g + 4 = 2

2g = 2 - 4

2g = -2

g = -2/2

g = -1

User Ellimilial
by
4.8k points